2019
DOI: 10.1371/journal.pone.0226908
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic of patulous eustachian tube patients diagnosed by the JOS diagnostic criteria

Abstract: ObjectiveThe objective is to describe characteristics of patients diagnosed with patulous Eustachian tube (PET) using the Diagnostic Criteria proposed by Japan Otological Society, and to evaluate the efficiency of objective tests to determine patent Eustachian tube.Study designRetrospective.SettingTertiary referral center.SubjectsA retrospective survey of medical records in Sen-En Rifu Hospital identified 78 ears of 56 patients with “Definite PET” diagnosed by the JOS Diagnostic Criteria between January 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
5
1
1
Order By: Relevance
“…The high prevalence of self-reported autophony symptoms found in our study is suggestive of PET in this patient population. Symptoms of autophony were often accompanied by symptoms compatible with "aural fullness," as previously described in patient cohorts with known PET (Kawamura et al, 2019;Ward et al, 2017). Weight loss from any cause is among the most frequently cited risk factors for PET.…”
Section: Discussionmentioning
confidence: 60%
“…The high prevalence of self-reported autophony symptoms found in our study is suggestive of PET in this patient population. Symptoms of autophony were often accompanied by symptoms compatible with "aural fullness," as previously described in patient cohorts with known PET (Kawamura et al, 2019;Ward et al, 2017). Weight loss from any cause is among the most frequently cited risk factors for PET.…”
Section: Discussionmentioning
confidence: 60%
“…Er wurde lediglich zur Schweregradeinteilung genutzt und nicht als eigenständiges diagnostisches Instrument. Dabei gaben 12,2 % keine relevanten Beschwerden im PHI-10 an und 58,1 % eine höchstgradige Beeinträchtigung [6].…”
Section: Introductionunclassified
“…Several diagnostic tools have been developed for the analysis of eustachian tube function, but none is reliable enough for gold‐standard diagnosis of patulous ET. The Japan Otological Society suggested reliable and reproducible clinical diagnostic criteria to classify patients with probable or certain PET 15,16 . The Eustachian Tube Dysfunction Patient Questionnaire (EDTQ‐7) self‐questionnaire 17 is also used to assess dysfunction of the ET, even though Van Roeyen et al 18 reported low performances in the diagnosis of PET.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Otological Society suggested reliable and reproducible clinical diagnostic criteria to classify patients with probable or certain PET. 15,16 The Eustachian Tube Dysfunction Patient Questionnaire (EDTQ-7) self-questionnaire 17 is also used to assess dysfunction of the ET, even though Van Roeyen et al 18 reported low performances in the diagnosis of PET. Sonotubometry has been used since 1978 5 for PET diagnosis.…”
Section: Comparison With Literature Datamentioning
confidence: 99%